(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In the Banking Industry, it has been in the form of E-Services, which is now replacing the traditional banking practice. E-Service has many benefits that add value to customers’ satisfaction in terms of a better quality of service offerings. E-Services can be done both online and offline. Examples of e-services are viewing account summary, overdraft details, transaction details, etc. through online and deposit account opening and deposit amend/renewal offline. E-Services are considered essential for accessing a more significant customer base, alternative communication channels to customers, and increasing services to customers. It is very convenient and has become an excellent comfort for busy customers. However, the banks are digitalizing their services and providing better E-Services to their customers; there is a lack of complete digitalization because of some illiterate customers. It is impossible to educate them all, but it is possible to train them by conducting training sessions. Also, the technological facts related to banks and their customers are hacked by some unauthorized persons, but this can be overcome by developing highly protected networks and applications used for E-Services in banking.